2022
DOI: 10.1002/er.7910
|View full text |Cite
|
Sign up to set email alerts
|

Atomic insights into combustion mechanism of nano‐aluminum hydride

Abstract: As an important hydrogen storage material, aluminum hydride is widely used

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Metals, especially aluminum, have high combustion enthalpy, which can increase the combustion temperature of the system, and aluminum combustion products are harmless and low cost, so they are widely used as fuel additives. An in-depth understanding of the pyrolysis or combustion of aluminum itself, [122][123][124][125][126][127][128][129] energetic materials/aluminum composites 112,[130][131][132][133][134][135] and small molecule/aluminum systems 123,134,[136][137][138][139][140] is of great interest.…”
Section: Pyrolysis and Combustion Mechanism Of Cl-20mentioning
confidence: 99%
See 1 more Smart Citation
“…Metals, especially aluminum, have high combustion enthalpy, which can increase the combustion temperature of the system, and aluminum combustion products are harmless and low cost, so they are widely used as fuel additives. An in-depth understanding of the pyrolysis or combustion of aluminum itself, [122][123][124][125][126][127][128][129] energetic materials/aluminum composites 112,[130][131][132][133][134][135] and small molecule/aluminum systems 123,134,[136][137][138][139][140] is of great interest.…”
Section: Pyrolysis and Combustion Mechanism Of Cl-20mentioning
confidence: 99%
“…When the temperature rises to 3500 K, the AHNP explodes and the morphology evolves into the fourth stage. Zhao et al 127 studied the evolution behavior of pure and core-shell AHNPs in an O 2 atmosphere. The results show that the oxidation of pure AHNPs begins on the surface of the particles and shows a non-uniform distribution.…”
Section: Pyrolysis and Combustion Mechanism Of Aerospace Fuels And En...mentioning
confidence: 99%
“…In particular, aluminum hydride (AlH 3 ) is highly regarded for its high hydrogen storage capacity and rapid dehydrogenation rate. Many enhancements have been made to improve the combustion efficiency and specific impulse of solid propellants after adding AlH 3 . In particular, in conventional ammonium perchlorate (AP)/hydroxyl-terminated polybutadiene (HTPB)-based rocket propellant, 18% Al has been fully replaced by AlH 3 , which results in a theoretical specific impulse that is increased by 10% . However, the low stability and poor compatibility of AlH 3 limit its wide application in solid propellants or high explosives .…”
Section: Introductionmentioning
confidence: 99%
“…AlH 3 exhibits a hydrogen content of 10 wt % or volumetric density (0.148 kg L –1 ), which is twice higher than that of liquid hydrogen. , It has been demonstrated that substituting Al with AlH 3 can significantly improve the specific impulses with reduced two-phase flow losses. Noteworthily, compared with traditional Al-based propellants, AlH 3 can reduce the adiabatic flame temperature as well (e.g., 3310 and 3912 K in 1.0 MPa air), resulting in less nozzle ablation, but the corresponding propellants are of higher specific impulse. ,, Moreover, according to the NASA CEA calculation results, replacing Al with AlH 3 could result in a 10% increase in specific impulse and a 5% reduction in flame temperature compared to the conventional Al/ammonium perchlorate (AP)/hydroxyl-terminated polybutadiene (HTPB) propellant. , The specific impulse can reach 296 s by replacing Al with AlH 3 in ammonium dinitramide (ADN)/glycidyl-azide polymer (GAP) propellants, 7.64–11.70% higher than that of ADN/Al/GAP- or AP/Al/HTPB-based propellants …”
Section: Introductionmentioning
confidence: 99%